Lymphocytic colitis: a retrospective clinical study of 199 Swedish patients. Issue 4 (11th March 2004) - Olesen, M; Eriksson, S; Bohr, J; Järnerot, G; Tysk, C
Abstract : Background: Lymphocytic colitis is characterised by chronic diarrhoea and specific microscopic changes in a macroscopically normal colonic mucosa. We report clinical features and treatment outcome in a large patient cohort. Methods: Patients were searched for in 24 Swedish gastroenterology clinics. The biopsy material was reassessed using strict histopathological criteria. Clinical data were obtained from medical notes. Results: Lymphocytic colitis was diagnosed in 199 cases. The female:male ratio was 2.4:1. Median age at diagnosis was 59 (48–70) years. The most frequent symptoms were diarrhoea (96%), abdominal pain (47%), and weight loss (41%). The course was chronic intermittent in 30% of patients, chronic continuous in 7%, and a single attack in 63%, and in these cases the disease duration was 6 (4–11) months. Seventy nine (40%) patients reported associated diseases, of which thyroid disorders, coeliac disease, and diabetes mellitus were the most common. In 34 first or second degree relatives of 24 (12%) patients, a family history of ulcerative colitis, Crohn's disease, collagenous colitis, or coeliac disease was reported. Drug induced disease was suspected in 19 (10%) patients. A non-significant peak of disease onset was seen in December-January. More than 80% of treated patients improved on corticosteroids, including budesonide. Conclusions: A family history of other bowel disorders is a new finding. The sudden onset and single attack of limited duration may support a possible infectious cause in some cases. Drugs may cause lymphocytic colitis.